The structure of Medicago truncatula δ1-pyrroline-5-carboxylate reductase provides new insights into regulation of proline biosynthesis in plants - Ruszkowski, Milosz; Nocek, Boguslaw; Forlani, Giuseppe; Dauter, Zbigniew (Frontiers in Plant Science, 2015)
The two pathways for proline biosynthesis in higher plants share the last step, the conversion of δ1-pyrroline-5-carboxylate (P5C) to L-proline, which is catalyzed by P5C reductase (P5CR, EC 1.5.1.2) with the use of NAD(P)H as a coenzyme. There is increasing amount of evidence to suggest a complex regulation of P5CR activity at the post-translational level, yet the molecular basis of these mechanisms is unknown. Here we report the three-dimensional structure of the P5CR enzyme from the model legume Medicago truncatula (Mt). The crystal structures of unliganded MtP5CR decamer, and its complexes with the products NAD+, NADP+ and L-proline were refined using high-resolution diffraction data (1.7, 1.85, 1.95 and 2.1 Å, respectively). Based on the presented structural data, the coenzyme preference for NADPH over NADH was explained, and NADPH is suggested to be the only coenzyme used by MtP5CR in vivo. Furthermore, the insensitivity of MtP5CR to feed-back inhibition by proline, revealed by enzymatic analysis, was correlated with structural features. Additionally, a mechanism for the modulation of enzyme activity by chloride anions is discussed, as well as the rationale for the possible development of effective enzyme inhibitors.